2005
DOI: 10.1111/j.1523-5378.2005.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Clinical Isolate of Urease‐Negative Helicobacter pylori and its Ability to Induce Gastric Ulcers in Mongolian Gerbils

Abstract: Fifteen Mongolian gerbils orally infected with 10(7) colony forming units of urease-negative H. pylori were killed at 4, 12, 24, 36 and 42 weeks (n = 3) after infection. Culture medium without urease-negative H. pylori was given to the Mongolian gerbils as control. H. pylori continued to exist in the subject's stomach and gastric ulceration was observed and compared with the control. Clinically obtained urease-negative H. pylori continued to exist for at least 42 weeks in the subject's stomach and it induced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
9
1
4
Order By: Relevance
“…In H. felis, a second urease system, UreA2B2, has been detected (180), but its function and regulation are currently unknown. One study showed that an H. pylori strain unable to produce functional urease was able to colonize and damage the gastric mucosa of Mongolian gerbils (150). This seems to contrast with results from many other studies stating that urease is essential for colonization of the stomachs of several animals, including gnotobiotic piglets (61).…”
Section: Virulence Factors Of Gastric Non-h Pylori Helicobacter Speciescontrasting
confidence: 47%
“…In H. felis, a second urease system, UreA2B2, has been detected (180), but its function and regulation are currently unknown. One study showed that an H. pylori strain unable to produce functional urease was able to colonize and damage the gastric mucosa of Mongolian gerbils (150). This seems to contrast with results from many other studies stating that urease is essential for colonization of the stomachs of several animals, including gnotobiotic piglets (61).…”
Section: Virulence Factors Of Gastric Non-h Pylori Helicobacter Speciescontrasting
confidence: 47%
“…Several studies have reported that H. pylori urease is related to the regulation of inflammation [72]. However, urease‐negative H. pylori can survive for at least 42 weeks in the gerbil stomach and H. pylori urease is not required for the formation of gastric ulcers in the Mongolian gerbil model [73]. Our results show that UreB has a higher intensity in isolates from patients with chronic gastritis or gastric cancer as compared with isolates from patients with ulcers, supporting the animal experiments [73].…”
Section: Discussionmentioning
confidence: 99%
“…The NH 3 produced by the action of urease neutralizes stomach acid and increases the pH of the surrounding cells [15]. In addition, urease participates in the inflammatory reaction and facilitates adhesion by interacting with the CD74 receptor on gastric epithelial cells [48, 50] isolated urease-negative H. pylori mutants from patients with peptic ulcers, and found that this strain successfully colonized the stomach of Mongolian gerbils and caused ulcers; therefore, the role of urease as a colonization factor is uncertain. The importance of motility as a colonization factor in H. pylori was first demonstrated in the study by [17], who demonstrated that germ-free piglets exhibited a higher infection rate when infected with motile H. pylori than when infected with the non-motile strain; moreover, the motile strain also colonized the stomachs for a longer duration in the stomach of germ-free piglets.…”
Section: Functions and Pathogenicity Of H Pylori Flagellamentioning
confidence: 99%